1998
DOI: 10.1017/s0033291797005813
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric after-effects of the Holocaust on the second generation

Abstract: Numerous studies conducted in clinical and community settings by researchers from different countries over a period of almost five decades, have conclusively shown protracted and disabling psychiatric effects among World War II Holocaust victims, formerly known as the concentration camp syndrome (e.g. Matussek, 1975; Eitinger & Krell, 1985; Eitinger & Major, 1993; Levav, 1998). The multiple and brutal trauma endured by the survivors during the war years were further compounded by earlier sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The majority of survivors' offspring develop into fully functioning and healthy people (Levav, Kohn, & Schwartz, 1998). Nonetheless, the conventionally structured survey measures that have delineated these generalities may fail to detect the subtleties of certain traumatic aftereffects.…”
Section: Holocaust Survivors and Their Offspringmentioning
confidence: 99%
“…The majority of survivors' offspring develop into fully functioning and healthy people (Levav, Kohn, & Schwartz, 1998). Nonetheless, the conventionally structured survey measures that have delineated these generalities may fail to detect the subtleties of certain traumatic aftereffects.…”
Section: Holocaust Survivors and Their Offspringmentioning
confidence: 99%
“…There is no consensus between the clinical observations and empiric research on the existence of long-term psychological effects on Holocaust survivors and their offspring [31,32]. Whereas case reports are indicative of transgenerational transmission of trauma [33], systematic studies have found no psychopathologic manifestations in the children of Holocaust survivors, except when they were exposed to life-threatening situations [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Their troublesome emotions and uncontrollable demons are experienced as "ego alien" as they seek treatment to "get rid of" the problems that plague them. The bulk of problems presented by second-generation survivors, however, falls into the category of personality challenges and generalized approaches to life which do not feature acute distress (Levav, Kohn, & Schwartz, 1998). As "children of the storm" (Downey, 2001), this generation suffered from an amalgamation of challenges aptly characterized as a "complex trauma" (Spermon, Darlington, and Gibney, 2010).…”
mentioning
confidence: 99%